Miss Camper - Fajardo, Kat, 1991- (Graphix, an imprint of Scholastic, 2025)
A companion to Miss Quinces, Kat Fajardo's bestselling, award-winning middle-grade graphic novel! Sue is heading to Camp Willow this summer! She's looking forward to hiking, archery, and making comics in the fresh air. She's especially excited about LARPing (live-action role-playing) and can't wait for the freedom of being away from home. But she won't be far from family because her big sister, Carmen, is a camp counselor and her little sister, Ester, is a fellow camper and won't give her any space! All Sue wants is to make memories with her friends, but they're assigned to only a few of the same activities. To make matters even worse, her best friend, Sam, has a best camp friend named Marisol? And Sue's good friend Izzy has a crush on Sue?! This summer isn't at all going as planned!